2015
DOI: 10.1155/2015/909724
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation of Antimony and Arsenic in Vegetables and Health Risk Assessment in the Superlarge Antimony-Mining Area, China

Abstract: Heavy metal pollution in soils caused by mining and smelting has attracted worldwide attention for its potential health risks to residents. This paper studies the concentrations and accumulations of Sb and As in both soils and vegetables and the human health risks of Sb and As in vegetables from Xikuangshan (XKS) Sb mine, Hunan, China. Results showed that the soils were severely polluted by Sb and As; Sb and As have significant positive correlation. Sb and As concentrations in vegetables were quite different: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 34 publications
0
21
1
Order By: Relevance
“…Regarding the other 2 trace elements included in the present study, the average concentration of Sb in roadside soils of community urban gardens in Canada [26] was lower than the results for most samples analyzed in Madrid, whereas Se concentrations of 2 sites in Pakistan irrigated with domestic wastewater [15] were above the maximum measured concentration in Madrid. Finally, a sampling campaign in the world's largest Sb mine showed that soil mean values of As and Sb were approximately 1 and 2 orders of magnitude larger, respectively, than in the present study [14]. When compared to the regional soil quality standards for human health protection and agriculture land use (i.e., 24 mg/kg, 0.8 mg/kg, and 85 mg/kg for As, Sb, and Se, respectively [27]), Sb exceeded the guideline value in 70% of the urban gardens studied, whereas just 1 sample exceeded the permissible level for As.…”
Section: Trace Element Concentrationscontrasting
confidence: 74%
See 1 more Smart Citation
“…Regarding the other 2 trace elements included in the present study, the average concentration of Sb in roadside soils of community urban gardens in Canada [26] was lower than the results for most samples analyzed in Madrid, whereas Se concentrations of 2 sites in Pakistan irrigated with domestic wastewater [15] were above the maximum measured concentration in Madrid. Finally, a sampling campaign in the world's largest Sb mine showed that soil mean values of As and Sb were approximately 1 and 2 orders of magnitude larger, respectively, than in the present study [14]. When compared to the regional soil quality standards for human health protection and agriculture land use (i.e., 24 mg/kg, 0.8 mg/kg, and 85 mg/kg for As, Sb, and Se, respectively [27]), Sb exceeded the guideline value in 70% of the urban gardens studied, whereas just 1 sample exceeded the permissible level for As.…”
Section: Trace Element Concentrationscontrasting
confidence: 74%
“…Sipter et al [9] found that in contaminated vegetable gardens near an abandoned mine in Hungary, most of the hazard index was attributable to Pb, with the As content of vegetables under the detection limit. However, considering just the ingestion of soil, the contribution of As to the aggregated hazard index was at least 1 order of magnitude higher Zeng et al [14] 94.44 1267.20…”
Section: Risk Assessmentmentioning
confidence: 91%
“…It has been observed that the water, vegetable fields, farmland, and soil in the tailings zone around XKS Antimony Mine are all seriously polluted [7][8][9][10][11][12][13]. PTEs released to water and soil have directly polluted crops, with PTEs in edible parts of foliage vegetables, fruits, and rhizomes grown in the affected areas of XKS mining area found to be several times higher than those in non-affected areas, among which, Sb and As are the two PTEs dominating this contamination [11,[14][15][16]. When an excessive amount of PTEs enter the human body, it will cause tumors and diseases to the liver, skin, and respiratory and cardiovascular systems, and even cancer [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Its longtime and large-scale mining and smelting has produced large amounts of smelting slag. With surface runoff and precipitation infiltration, harmful elements like Sb and the associated elements As and Hg have been released, threatening the environment and human beings [10][11][12][13][14]. When an excessive amount of Sb, As, or Hg enters the human body, it will cause diseases to the liver, skin, tumors, respiratory and cardiovascular systems, and even cancer [15][16][17][18][19].…”
mentioning
confidence: 99%